Recognition of the 24-hour Noise Exposure of a Human - Tomasz KORBIEL; Bartłomiej STĘPIEŃ; Wojciech BATKO; Robert BARAŃSKI; Dominik MLECZKO; Paweł PAWLIK; Jędrzej BLAUT (Archives of Acoustics, 2017)
The civilisation progress has caused noise to become one of essential pathogenic and life comfort decreasing factors. There are several legal regulations aimed at controlling the noise influence on humans. Assessment of the twenty-four-hour influence of noises in various environments constitutes an essential problem. The answer can be supplied by 24-hour monitoring of the sound pressure. This paper is an attempt to learn the real loading of humans by noises. A personal noise indicator was used in measurements. The human 24-hour activity was divided into cycles allowing to model noise hazards. The collected data, even though they did not signal exceeding of individual standards, in the 24-hour period indicated the essential noise influence. These results indicate the need of investigations to recognise the 24-hour noise load of a human, with taking into account various forms of their activity and the need of rest.